Adorno und die Kritik der weiblichen Lebensformen - Salima Naït Ahmed (Recherches Germaniques)
The Adornian critique of the capitalist form of life has recently been revived by several authors from the tradition of German critical theory. However, the gender dimension of the adornian critique of forms of life is still ignored, despite the original insights it provides for the understanding of capitalism and its particular relationship to patriarchy. The article therefore proposes to recompose the singular critique of female forms of life in Adorno’s Minima Moralia, while showing the heuristic contribution of the notion of the form of life to feminist thought. However, in order to ensure that the notion retains its truly critical potential, it will also be necessary to question the androcentric dimension of Adorno’s reflection, particularly by revisiting certain aporias of its Freudian inspired anthropology. In doing so, what will be at stake is “the critique of Adorno as to better learn from him” and to better put his sharp critique at the service of feminist questions of our time.